Performance Management Cycle Analysis At Teluk Bakau Bay View Seafood Restaurant - Refia Dina Amanda; Dindra Alsyah; Lili; Rizky Gustaman; Satriadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the performance management cycle at Seafood Restaurant Teluk Bakau Bay View, Bintan Regency. Using a qualitative research method, data were collected through in-depth interviews and observations. The sample used was purposive sampling with 2 informants, namely the restaurant owner Mr. Gunawan and an employee named Kelvin. The data analysis used is descriptive analysis. The research results show that the management cycle implemented at Seafood Restaurant Teluk Bakau Bay View has been carried out well. This can be seen from the planning that sets goals for the consistency of employee performance. Monitoring is conducted daily in terms of revenue, employee performance, customer feedback, and achievement of sales targets. Employee reviews at Seafood Restaurant Teluk Bakau Bay View are conducted by re-evaluating the results of daily employee performance monitoring, and assessments are made from these monitoring results to determine rewards or sanctions for employees. The awards given to employees are based on the review conducted from the evaluation results, where these awards are in the form of cash bonuses added to the basic salary.